1996
DOI: 10.1002/j.1460-2075.1996.tb00911.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct inhibition of the signaling functions of the mammalian target of rapamycin by the phosphoinositide 3-kinase inhibitors, wortmannin and LY294002.

Abstract: The immunosuppressant, rapamycin, inhibits cell growth by interfering with the function of a novel kinase, termed mammalian target of rapamycin (mTOR). The putative catalytic domain of mTOR is similar to those of mammalian and yeast phosphatidylinositol (PI) 3‐kinases. This study demonstrates that mTOR is a component of a cytokine‐triggered protein kinase cascade leading to the phosphorylation of the eukaryotic initiation factor‐4E (eIF‐4E) binding protein, PHAS‐1, in activated T lymphocytes. This event promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
494
2
6

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 678 publications
(543 citation statements)
references
References 58 publications
41
494
2
6
Order By: Relevance
“…In tissue culture cells and in cell free systems, the dependence of mitosis on the completion of S phase (Schlegel and Pardee, 1986) as well as the G2 DNA damage checkpoint (Downes et al, 1994) can be uncoupled by ca eine. We found that levels of ca eine which bypass the replication checkpoint inhibited both basal and DNA-stimulated ATR kinase activity, almost to levels achieved with another inhibitor of PIK family kinases, LY294002 (Brunn et al, 1996). We suggest that ATR may be one target for the ca eine-mediated bypass of S phase and G2 checkpoints.…”
Section: Discussionmentioning
confidence: 68%
“…In tissue culture cells and in cell free systems, the dependence of mitosis on the completion of S phase (Schlegel and Pardee, 1986) as well as the G2 DNA damage checkpoint (Downes et al, 1994) can be uncoupled by ca eine. We found that levels of ca eine which bypass the replication checkpoint inhibited both basal and DNA-stimulated ATR kinase activity, almost to levels achieved with another inhibitor of PIK family kinases, LY294002 (Brunn et al, 1996). We suggest that ATR may be one target for the ca eine-mediated bypass of S phase and G2 checkpoints.…”
Section: Discussionmentioning
confidence: 68%
“…Furthermore, suppression of PI3Ks by wortmannin led to inhibition of PLCg1 phosphorylation (left panel) suggesting involvement of PI3Ks in its stimulation. The downregulation of S6 phosphorylation detected here is most likely result of inactivation of multiple upstream molecules-PI3Ks, PLC-g, Akt, but also consequence of direct suppression of mTOR by wortmannin because its catalytic domain shares high homology to the lipid kinase domain of PI3Ks (Brunn et al, 1996). Downregulation of p70S6-kinase/S6 by inhibition of PLC-g1 signaling Activation of PLC-g results in hydrolysis of phosphatidylinositol 4,5-bisphosphate (PIP 2 ) to diacylglycerol and inositol 1,4,5-triphosphate (IP 3 ), which in turn leads to activation of different PKC isoforms and increase in Ca-dependent signaling, including Ca/Calmodulin-dependent-kinase (CaMK) (Rhee et al, 2000;Rhee, 2001) (please see the scheme in Figure 4a).…”
Section: Resultsmentioning
confidence: 79%
“…Not surprisingly, considering the similarity between the PI3K and PIKK catalytic domains, wortmannin also irreversibly inhibits PIKK family members. DNA-PK is the most sensitive (IC 50 =16 nM), followed by SMG-1 (IC 50 ∼ 60 nM), ATM (IC 50~1 00-150 nM), mTOR (IC 502 00 nM) and ATR (IC 50 =1.8 μM) [65][66][67][68]. Wortmannin forms a covalent bond with mTOR, presumably at Lys2187 in the ATP-binding site [65].…”
Section: Mtor Kinase Inhibitorsmentioning
confidence: 99%